Enhanced pH-Mediated Stacking of Anions for Capillary Electrophoresis Incorporating a Dynamic pH Junction - Arnett, Stacy D. (2007)
A technique has been developed to enhance analyte focusing for capillary electrophoresis for the analysis of physiological samples. High-ionic strength samples are titrated to low-ionic strength on-line using pH-mediated sample stacking in conjunction with a dynamic pH junction. This method concentrates analytes by reducing their electrophoretic mobility during field-amplification. Parameters responsible for enhanced focusing were investigated, and an enhanced pH-mediated stacking method was optimized for anionic nucleosides. The process results in ultra-narrow peak widths, for example, 0.28 s for thymidine with a 10-minute analysis time. Peak width and resolution with the enhanced stacking method were also compared to normal base stacking and electrokinetic injection. With this technique, mass-loading capacity can be increased without degradation in peak shape and resolution is dramatically improved.